2009
DOI: 10.1038/cgt.2009.44
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal administration of telomerase-specific oncolytic adenovirus sensitizes ovarian cancer cells to cisplatin and affects survival in a xenograft model with peritoneal dissemination

Abstract: Despite tremendous development in chemotherapy for ovarian cancer over the past few decades, the prognosis of advanced cases with massive peritoneal dissemination is still unsatisfactory, and novel treatment modalities that can combine with chemotherapy are urgently needed. We recently developed virotherapy for solid tumors using telomerase-specific replication-selective adenoviruses (Telomelysin: OBP-301), in which the human telomerase reverse transcriptase (hTERT) gene promoter has been inserted to direct tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 29 publications
(54 reference statements)
2
41
0
Order By: Relevance
“…Although multimodal approaches such as intraperitoneal chemotherapy and hyperthermic intraperitoneal chemoperfusion (HIPEC) have been explored32, there is no standard treatment to effectively prevent peritoneal dissemination. We recently reported that intraperitoneal administration of OBP-301 in combination with cisplatin efficiently suppresses the peritoneal dissemination of ovarian cancer cells in vivo 33. Intraperitoneal administration of OBP-401 is also useful for in vivo identification of peritoneally disseminated human cancer cells in fluorescence-guided surgery34.…”
Section: Discussionmentioning
confidence: 99%
“…Although multimodal approaches such as intraperitoneal chemotherapy and hyperthermic intraperitoneal chemoperfusion (HIPEC) have been explored32, there is no standard treatment to effectively prevent peritoneal dissemination. We recently reported that intraperitoneal administration of OBP-301 in combination with cisplatin efficiently suppresses the peritoneal dissemination of ovarian cancer cells in vivo 33. Intraperitoneal administration of OBP-401 is also useful for in vivo identification of peritoneally disseminated human cancer cells in fluorescence-guided surgery34.…”
Section: Discussionmentioning
confidence: 99%
“…Telomelysin (OBP-301), a telomerase-specific replicationselective adenovirus, has been shown to induce notable tumor-targeted oncolysis in a broad range of human cancers Watanabe et al 2006;Hashimoto et al 2008;Hioki et al 2008;Takakura et al 2010), and a phase I trial in patients with advanced solid tumors is currently in progress . In this study, we showed for the first time that this novel potential anti-tumor adenovirus, Telomelysin, induces apoptotic cell death-mediated oncolysis in human osteosarcoma both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…We have therefore developed an oncolytic adenovirus (Telomelysin, in which the hTERT promoter controls the expression of E1A and E1B genes that are linked with an internal ribosome entry site (IRES; Kawashima et al 2004). Our previous studies demonstrated that Telomelysin exhibits tumor-restricted replication and excellent cytotoxicity against many different types of cancers, but not of normal cells or tissues Watanabe et al 2006;Hashimoto et al 2008;Hioki et al 2008;Takakura et al 2010). To the best of our knowledge, Telomelysin is the first hTERT-specific oncolytic adenovirus to be tested in a phase I clinical trial for various types of solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…High-dose combination therapy was actually unable to further increase the levels of tumor cell death already being induced by low-dose chemovirotherapy 59, 60. Furthermore, virus-mediated chemosensitization was shown to be powerful enough to render chemotherapy-resistant tumor cells sensitive for low-dose chemotherapy 61, 62…”
Section: Discussionmentioning
confidence: 99%